2007
DOI: 10.1243/09576509jpe445
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental study of unsteady flow in a centrifugal fan

Abstract: In the current work, computational fluid dynamics (CFD) technique coupled with experimental investigations has been used in order to study the complex phenomena related to the unsteady flow in a centrifugal fan.The studied phenomena are the interactions and unsteadiness induced by the rotating blades motion relatively to the volute and their impact on the aeroacoustic behaviour of the fan. Thus, three-dimensional and two-dimensional unsteady simulations have been carried out using unsteady Reynolds averaged Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…The grid refinement has been studied and adapted to the flow morphology minimizing element distortion and to achieve required resolution in high-gradient regions. The details of this study are reported in previous papers by Younsi et al [7,8]. An example of the retained grid mesh International Journal of Rotating Machinery is shown in Figure 6.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…The grid refinement has been studied and adapted to the flow morphology minimizing element distortion and to achieve required resolution in high-gradient regions. The details of this study are reported in previous papers by Younsi et al [7,8]. An example of the retained grid mesh International Journal of Rotating Machinery is shown in Figure 6.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…And most of them focus their attentions on the FC multi-blade, BC blades and radial blades centrifugal fans. With respect to the noise generation mechanism of centrifugal fans, Velarde-Suárez et al [4,5], Younsi et al [6] and Lin et al [7] studied the unsteady flow and aerodynamic tonal noise of FC multi-blade centrifugal fans. In the other paper, Sasaki [8] explored the influence of Karman Vortex Street on the broadband noise generated from an FC multi-blade fan.…”
Section: Introductionmentioning
confidence: 99%
“…Sampling begins when it is stable after calculation for 10 cycles. Figure 3 shows the diagram of the experimental system for the aerodynamic performance, where an outlet chamber is established to measure the related physical parameters [8]. The discharge static pressure of the tested fan is measured using a pressure transducer installed in the chamber.…”
Section: Boundary Condition and Settingmentioning
confidence: 99%